Outcomes of patients with severe tricuspid regurgitation and congestive heart failure - Kadri, Amer N. (2019)
Objectives A substantial number of patients with severe tricuspid regurgitation (TR) and congestive heart failure (CHF) are medically managed without undergoing corrective surgery. We sought to assess the characteristics and outcomes of CHF patients who underwent tricuspid valve surgery (TVS), compared with those who did not. Methods Retrospective observational study involving 2556 consecutive patients with severe TR from the Cleveland Clinic Echocardiographic Database. Cardiac transplant patients or those without CHF were excluded. Survival difference between patients who were medically managed versus those who underwent TVS was compared using Kaplan-Meier survival curves. Multivariate analysis was performed to identify variables associated with poor outcomes. Results Among a total of 534 patients with severe TR and CHF, only 55 (10.3%) patients underwent TVS. Among the non-surgical patients (n=479), 30% (n=143) had an identifiable indication for TVS. At 38 months, patients who underwent TVS had better survival than those who were medically managed (62% vs 35%; p<0.001). On multivariate analysis, advancing age (HR: 1.23; 95% CI 1.12 to 1.35 per 10-year increase in age), moderate (HR: 1.39; 95% CI 1.01 to 1.90) and severe (HR: 2; 95% CI 1.40 to 2.80) right ventricular dysfunction were associated with higher mortality. TVS was associated with lower mortality (HR: 0.44; 95% CI 0.27 to 0.71). Conclusion Although corrective TVS is associated with better outcomes in patients with severe TR and CHF, a substantial number of them continue to be medically managed. However, since the reasons for patients not being referred to surgery could not be ascertained, further randomised studies are needed to validate our findings before clinicians can consider surgical referral for these patients.